Enhancing Junior High School Students’ English Proficiency Through Interactive Case-Based Learning - Roswita Aboe; Naniek Jusnita; Asrul M. Syawal; Harriot Beazley (JOLLT Journal of Languages and Language Teaching, 2026)
The integration of learner-centered pedagogy and digital technology has become increasingly important for improving English language learning outcomes. Therefore, this study aimed to investigate the effectiveness of integrating CBL with interactive media to enhance students’ English language proficiency for junior high school students. The study employed an exploratory case study design using mixed methods. Participants included junior high school students and English teachers involved in the implementation of CBL supported by interactive media. Data were collected through pre- and post-tests, questionnaires, classroom observations, and interviews. Instrument reliability analysis indicated acceptable internal consistency (Cronbach’s α = 0.7613). The findings revealed substantial improvements in students’ learning outcomes. The mean score increased from 52.00 on the pre-test to 83.00 on the post-test, exceeding the minimum passing criterion of 75.00. Learning performance also became more consistent, as reflected in the reduction of the standard deviation from 6.51 to 3.61 and the increase in minimum scores from 45 to 74. Questionnaire results showed that student engagement demonstrated the strongest construct validity, while perceived improvement showed adequate validity and motivation exhibited a weaker correlation. Qualitative evidence further indicated higher levels of engagement, clearer understanding of learning materials, greater confidence in English use, and more active classroom interaction. The study concludes that integrating CBL with interactive media effectively enhances English proficiency, engagement, and learner confidence. These findings provide practical guidance for implementing technology-enhanced, learner-centered English instruction in secondary education.